Development of a microbiome for phenolic metabolism based on a domestication approach from lab to industrial application - Wei Zhao; Liuyang Shi; Yifan Han; Xingbiao Wang; Jingjing Wang; Song Xu; Xiaoxia Zhang; Zhiyong Huang (Communications Biology)
Abstract Despite a lot of efforts devoted to construct efficient microbiomes, there are still major obstacles to moving from the lab to industrial applications due to the inapplicability of existing technologies or limited understanding of microbiome variation regularity. Here we show a domestication strategy to cultivate an effciient and resilient functional microbiome for addressing phenolic wastewater challenges, which involves directional domestication in shaker, laboratory water test in small-scale, gas test in pilot scale, water test in pilot scale, and engineering application in industrial scale. The domestication process includes the transition from water to gas, which provided complex transient environment for screening of a more adaptable and robust microbiome, thereby mitigating the performance disparities encountered when transitioning from laboratory experimentation to industrial engineering applications. Within the domestication and application processes for treating phenolic resin wastewater, a powerful functional microbiome was built by self-assembly. This leads to an augmented biodiversity and the development of more intricate phenol and formaldehyde metabolic pathways. The incorporation of increased stochastic processes and random network characteristics further suggested the stability of the microbial community during the application phase. This study elucidates the self-assembly process of microbial communities during the artificial construction process, showcasing their adaptive evolution under different adverse conditions. It serves as a noteworthy case study for the artificial construction of a microbiome for the engineering application of treating industrial wastewater.